2017
DOI: 10.7759/cureus.1468
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude of Teenagers Towards Electronic Cigarettes in Karachi, Pakistan

Abstract: IntroductionStudies have shown that electronic cigarettes have gained immense popularity and their use has increased dramatically all over the world. However, little is known about the knowledge and attitudes towards e-cigarettes in third world countries such as Pakistan. The aim of this study was to determine the perceptions of teenagers in Karachi regarding e-cigarettes and whether the differences in said perceptions were affected by gender and level of education.MethodsWe conducted a cross-sectional study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
0
16
0
2
Order By: Relevance
“…The percentage of respondents in our study who were unsure of the contents inside the cigarette was similar to the findings in a study in Pakistan. 34 When asked whether it contained nicotine, slightly more than half (53.1%) answered 'yes' and only 28.5% respondents answered that it does not contain tar.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The percentage of respondents in our study who were unsure of the contents inside the cigarette was similar to the findings in a study in Pakistan. 34 When asked whether it contained nicotine, slightly more than half (53.1%) answered 'yes' and only 28.5% respondents answered that it does not contain tar.…”
Section: Discussionmentioning
confidence: 98%
“…The finding was in line with another study that reported young women have relatively poor knowledge on smoking behavior. 34,38,39 This is probably due to the differences in their risk perception and risk-taking behaviour, which may influence the male participants to explore more information on risk-taking behaviour. 40 Our results however differs from another study which emphasized that female participants have higher knowledge on smoking than the male, but their finding was not significant.…”
Section: Association Between Socio-demographic Factors and Knowledge Attitude And Practicementioning
confidence: 99%
“…Parents were provided with a self-administered questionnaire constructed after a thorough literature review. 15,[32][33][34] The questionnaire was sent to two experts in the field for content validity, and they interviewed 20 mothers for face validity. The questionnaire was modified accordingly.…”
Section: Methodsmentioning
confidence: 99%
“…Paparan informasi rokok elektronik pada remaja banyak berasal dari media elektronik (Putra et al, 2017;Wagoner et al, 2019), teman (Nurmalasari, Nirmalasari, & Verawati, 2018;Putra et al, 2017;Shaikh et al, 2017)…”
Section: Pendahuluanunclassified
“…Sejalan dengan studi yang dilakukan di Pakistan, walaupun mayoritas remaja tahu e-cig, namun tidak memahami informasi yang lengkap dan komprehensif tentang kandungannya (Shaikh et al, 2017), bahaya dan ilusi yang ditawarkan e-cig kepada remaja (Ferkol et al, 2018). Ditambah lagi kesimpang siuran informasi dan sumber informasi yang tidak tepat yang diakses oleh remaja menjerumuskan remaja ke persepsi dan perilaku yang salah dan merugikan.…”
Section: Pembahasanunclassified